The development of antenna complexes of barley (Hordeum vulgare cv. Akcent) under different light conditions as judged from the analysis of 77 K chlorophyll a fluorescence spectra - Cajánek, M; Navrátil, M; Kurasová, I; Kalina, J; Spunda, V (Photosynthesis research, 2002)
Using 77 K chlorophyll a (Chl a) fluorescence spectra in vivo, the development was studied of Photosystems II (PS II) and I (PS I) during greening of barley under intermittent light followed by continuous light at low (LI, 50 mumol m(-2) s(-1)) and high (HI, 1000 mumol m(-2) s(-1)) irradiances. The greening at HI intermittent light was accompanied with significantly reduced fluorescence intensity from Chl b excitation for both PS II (F685) and PS I (F743), in comparison with LI plants, indicating that assembly of light-harvesting complexes (LHC) of both photosystems was affected to a similar degree. During greening at continuous HI, a slower increase of emission from Chl b excitation in PS II as compared with PS I was observed, indicating a preferred reduction in the accumulation of LHC II. The following characteristics of 77 K Chl a fluorescence spectra documented the photoprotective function of an elevated content of carotenoids in HI leaves: (1) a pronounced suppression of Soret region of excitation spectra (410-450 nm) in comparison with the red region (670-690 nm) during the early stage of greening indicated a strongly reduced excitation energy transfer from carotenoids to the Chl a fluorescing forms within PS I and PS II; (2) changes in the shape of the excitation band of Chl b and carotenoids (460-490 nm) during greening under continuous light confirmed that the energy transfer from carotenoids to Chl a within PS II remained lower as compared with the LI plants.